Peningkatan Literasi Keuangan Syariah Melalui Pelatihan dan Pendampingan Masyarakat Kabupaten Bekasi - Sakum; Sukron Mamun; Ali Nur Ahmad; Sarwo Edy; Hamdan Ainulyaqin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial literacy in Indonesia, especially in the context of sharia financial literacy, shows an alarming level. Financial literacy includes the ability to read, analyze, manage and communicate personal financial conditions. The World Bank survey places Indonesia in the third lowest ranking globally in terms of financial literacy, behind India and China. Data from the Financial Services Authority (OJK) shows that in 2013 and 2016, only around 21.84% and 29.66% of the Indonesian adult population had adequate financial literacy, with the figure among MSMEs even lower, namely 18.71%. An OJK webinar in 2022 revealed that the sharia economic literacy index had only reached 23.3%, far below the national financial literacy index of 49%. This imbalance highlights the need for broader educational efforts to increase public understanding of Islamic financial products. Even though financial education is the key to increasing literacy, in Indonesia, financial education is still rare in schools and universities. Developed countries have actively promoted financial education, while big challenges still exist in Indonesia. In the Islamic context, financial literacy also includes understanding muamalah maaliyah law to ensure halal and fair transactions. This research aims to explore and understand aspects of sharia financial literacy and inclusion through a qualitative approach, with observations and literature reviews in Bekasi Regency. It is hoped that this research can provide in-depth insights and recommendations to increase sharia financial literacy and inclusion more effectively.